Chicken Eggshell Waste as a Vegetable Breeding Media at the Culinary Department of SMK Negeri 4 Yogyakarta - Heni Purwanti; Yuni Heruwati (Journal of Vocational Education Studies, 2020)
The culture of managing waste at the culinary department of SMK Negeri 4 Yogyakarta—a school of Adiwiyata which has a good environment for students to learn and to foster a sense of loving the environment—is by utilizing the organic waste, one of which is the chicken eggshell waste. Chicken eggs are widely used to process foods in the culinary department of SMK Negeri 4 Yogyakarta. Various types of processed foods use chicken eggs as the main ingredient or as supporting/additional material. The need for chicken eggs is quite large every day, causing an abundance of chicken eggshell waste in the culinary department of SMK Negeri 4 Yogyakarta. This experimental study aims to utilize chicken eggshell waste as a vegetable nursery media by direct practice of nursery vegetable plants with chicken eggshell media. The results showed that eggshells can be used as a plant medium and even the growth of seedlings looks better and fertile. This is probably due to the content of calcium, phosphorus, nitrogen, and potassium in eggshells.